P. Tychyna and R. M. Rilke: poetic prayer of the artists (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article analyzes meaning of prayer in the poetry of Pavlo Tychyna and Rainer Maria Rilke. Emphasis is drawn to the image of God in the verses of poets and modification of the genre in the biblical prayer, the prayer of appeal, prayer request, prayer dialogue.